Keuangan-Perilaku Berhutang : Menakar Faktor-faktor Penentunya - Aprih Santoso; Sri Yuni Widowati; Nunik Kusnilawati (Owner : Riset dan Jurnal Akuntansi, 2022)
The purpose of this research is to examine how financial-debt behavior is influenced by perceived control behavior and debt intention, seta and debt intention are influenced by perceived control behavior. In this study, debt intention as a mediating variable on debt behavior is influenced by perceived control behavior for small entrepreneurs in the city of Semarang. The research population includes all small entrepreneurs who take credit from the Wibawa in the city of Semarang, amounting to 395 people. The number of samples is 103 people (based on the Slovin formula). The sample selection method is accident sampling. The relationship model of the variables will be analyzed using Partial Least Square (PLS). The results of research using Partial Least Square (PLS) analysis show that debt behavior is influenced by perceived control behavior and debt intentions. Intention to owe is influenced by perceived control behavior. Debt intention is able to mediate debt behavior which is influenced by perceived control behavior for small entrepreneurs in the city of Semarang.